SELF-DIRECTED ENGLISH LEARNING THROUGH SOCIAL MEDIA: A SYSTEMATIC LITERATURE REVIEW - Berlin, Astri Winandari; Wibowo, Enggar Pangesti; Purnawarman, Pupung (STKIP Persada Khatulistiwa Sintang, 2025)
This paper presents a systematic literature review of studies on self-directed English learning through social media. Using the Systematic Literature Review method, data were gathered from three prominent journal databases: Scopus, Google Scholar, and Emerald Insight. The search strategy targeted publications from 2020 to June 11, 2024, selecting 32 relevant studies for analysis. The review identifies thirteen social media platforms, with YouTube, Instagram, and WhatsApp emerging as the most widely used. It explores how students engage in various learning activities, including following educational accounts, watching English videos, and participating in discussions. The findings underscore the significant benefits of integrating social media into self-directed English learning, such as improved language skills, enhanced engagement, and flexible learning opportunities. However, the review also highlights challenges such as distractions and privacy concerns, emphasizing the importance of educators and policymakers in developing strategies to address these issues. By promoting digital literacy and providing guidance and support, educators can help students overcome these challenges and optimize their use of social media for effective self-directed English learning.